2018
DOI: 10.1093/biolre/ioy129
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine supplementation enhances development of in vitro-produced porcine embryos and increases leucine consumption from the medium†

Abstract: Improper composition of culture medium contributes to reduced viability of in vitro-produced embryos. Glutamine (Gln) is a crucial amino acid for preimplantation embryos as it supports proliferation and is involved in many different biosynthetic pathways. Previous transcriptional profiling revealed several upregulated genes related to Gln transport and metabolism in in vitro-produced porcine blastocysts compared to in vivo-produced counterparts, indicating a potential deficiency in the culture medium. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 55 publications
4
52
1
Order By: Relevance
“…Also, it was observed that pig embryos depended more on glutamine metabolism than human, murine, and bovine embryos (Krisher, Heuberger, et al, ). As previously described, uptake and production of amino acids have an important role in preimplantation development (Bauer et al, ; Brison et al, ; Chen et al, ; Hemmings, Leese, & Picton, ; Prather, Redel, Whitworth, & Zhao, ; Redel et al, ). Metabolomics profiling data can indicate potential biomarkers of embryo quality to improve implantation and pregnancy rates after culturing embryos in vitro (Krisher, Schoolcraft, et al, ; Wale & Gardner, ).…”
Section: Transcriptomic and Metabolomic Approaches To Understand Preimentioning
confidence: 81%
See 4 more Smart Citations
“…Also, it was observed that pig embryos depended more on glutamine metabolism than human, murine, and bovine embryos (Krisher, Heuberger, et al, ). As previously described, uptake and production of amino acids have an important role in preimplantation development (Bauer et al, ; Brison et al, ; Chen et al, ; Hemmings, Leese, & Picton, ; Prather, Redel, Whitworth, & Zhao, ; Redel et al, ). Metabolomics profiling data can indicate potential biomarkers of embryo quality to improve implantation and pregnancy rates after culturing embryos in vitro (Krisher, Schoolcraft, et al, ; Wale & Gardner, ).…”
Section: Transcriptomic and Metabolomic Approaches To Understand Preimentioning
confidence: 81%
“…However, in contrast to the arginine‐treated embryos, embryos cultured with supplemental glycine did not establish pregnancies after 11 embryo transfers (Redel et al, ). Similar to the arginine story, supplementation of glutamine to the porcine embryo culture medium improved development to the blastocyst stage, reduced transcript levels of a glutamate transporter, SLC1A1 , to a level more similar to in vivo‐derived embryos, promoted leucine consumption from the medium, and resulted in birth of live piglets (Chen et al, ).Furthermore, the subunit of the granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) receptor (CSFR) was more abundant in IVC embryos when compared to IVV embryos (Bauer et al, ). The addition of GM‐CSF during culture in vitro increased blastocyst rates and total cell number of IVF and SCNT‐derived embryos.…”
Section: Transcriptomic and Metabolomic Approaches To Understand Preimentioning
confidence: 99%
See 3 more Smart Citations